RAPID INTERVENTION WITH GLYCERYL TRINITRATE IN HYPERTENSIVE STROKE TRIAL-2 (RIGHT-2): SAFETY AND EFFICACY OF TRANSDERMAL GLYCERYL TRINITRATE, A NITRIC OXIDE DONOR. Issue 9 (18th August 2016) - Bath, Philip M W; Dixon, Mark; Appleton, Jason; Scutt, Polly; England, Timothy; Foster, Hayley; Howard, Harriet; Jarvis, Malcolm; Montgomery, Alan; Pocock, Stuart; Potter, John; Price, Christopher; et al.
Abstract : Rationale: High blood pressure (BP) is common in acute stroke and is associated with poor outcome. Previous hospital-based trials testing the effects of BP lowering on functional outcome have been inconclusive. The PIL-FAST and RIGHT pilot trials confirmed the feasibility of performing single-centre ambulance-based stroke trials in the UK. In both RIGHT and a subgroup of patients recruited within 6 hours into the large ENOS trial, transdermal glyceryl trinitrate (GTN), a nitric oxide donor, lowered BP and reduced death or disability. Based on these results, RIGHT-2 aims to test the safety and efficacy of transdermal GTN in the pre-hospital setting. Methods: Paramedics from 7 UK ambulance services serving 40 comprehensive or primary stroke care centres will screen, consent, randomise and treat 850 patients presenting within 4 hours of FAST-positive stroke and with systolic BP >120 mm Hg. Treatment will comprise GTN or similar sham patch, and will be continued in hospital for 3 days. The primary outcome will be the modified Rankin Scale at day 90. Secondary outcomes include vascular events, disability, quality of life, mood and cognition. Neuroimaging and biomarkers will examine potential mechanisms of action. Status: Recruitment commenced in October 2015. Challenges with the trial and baseline characteristics of the first recruited patients will be presented. Funding: British Heart Foundation.